A fortune for your disaster - Abdurraqib, Hanif, 1983- (Tin House Books, 2019)
In his much-anticipated follow-up to The Crown Ain't Worth Much, poet, essayist, biographer, and music critic Abdurraqib has written a book of poems about how one rebuilds oneself after a heartbreak, the kind that renders them a different version of themselves than the one they knew.